KETAKSAMAAN INTEGRAL GRONWALL-BELLMAN UNTUK FUNGSI BERPANGKAT - Rijoly, Monalisa E.; Wattimanela, Henry J.; Matakupan, Rudy W. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2011)
Integral inequality of Gronwall-Bellman is known as an integral inequality which consists of differential and integral forms. Integral inequality of Gronwall-Bellman involving several functions that some definite condition hold and integral values of these functions. In addition, the integral inequality of Gronwall-Bellman shows that if a function is bounded to a certain integral values then that function is also bounded for the other conditions, that is the exponential of integral. Furthermore, by adding some specific conditions the integral inequality of Gronwall-Bellman can be extended to the case of power functions.